Minutes [from] the Association of Physician Assistant Programs, April 13, 1973 - Greenberg, Suzanne B. (1973)
Minutes of the Annual Meeting of the Association of Physician Assistant Programs held April 13, 1973 at the Ramada Inn in Wichita Falls, TX during the First National Conference on New Health Practitioners. The Treasurer's report indicated that the Association had a balance of $1,824 and the Registry $853 on hand. Items discussed included: (1) Admission requirements for program membership; (2) relationships with other medical organizations - representation on JRC for accreditation; (3) by-law changes to allow individual membership in the Association; (4) increase dues to $125 per program; (5) meeting conjunctively with AAMC at their fall meeting in November 1973 in Washington, DC; (6) appointment of conference planning committee; (7) report on cost of First Annual Conference; (8) election of new officers for 1974-1975; (9) status update on Registry; (10) feasibility of a joint national office for AAPA and APAP; and (10) recognition of the Academy as "the appropriate organization to represent physician assistants in the United States." A form to join the Association as an individual member is attached to the minutes - dues were $25.